Local Practical Religious Moderation in Indonesia: A Case Study of Churches in Getasan District, Semarang Regency - Nugroho, Fibry Jati; Sari, Dwi Novita (KAMASEAN: Jurnal Teologi Kristen, 2023)
This paper is a qualitative study that describes the phenomenon of religious moderation in the Getasan District, Semarang Regency, Central Java Province. Many mass media highlight the high tolerance in the Getasan area, which makes it interesting to investigate it deeper related to religious management in the community. By using the analysis of Miles and Huberman and mixing it with the perspective of Citizenship Pluralism, the results showed that Christian religious leaders taught church members about three things, including doctrinal teaching that educated the law of love as their foundation, contextualization by mixing and matching culture in the development of faith and social devotion in terms of religiosity in society. From the perspective of civic pluralism, Christian religious leaders carried out recognition, representation, and redistribution as a way of teaching religious moderation in society, which aims to create social harmony in society. A good understanding of religious moderation, by linking religious texts and religious contexts, then internalizing it into their daily lives, makes church members have an important role in creating harmony in the community in Getasan District, Semarang Regency.